Moral courage in nursing: A concept analysis. (December 2017) - Numminen, Olivia; Repo, Hanna; Leino-Kilpi, Helena
Background: Nursing as an ethical practice requires courage to be moral, taking tough stands for what is right, and living by one's moral values. Nurses need moral courage in all areas and at all levels of nursing. Along with new interest in virtue ethics in healthcare, interest in moral courage as a virtue and a valued element of human morality has increased. Nevertheless, what the concept of moral courage means in nursing contexts remains ambiguous. Objective: This article is an analysis of the concept of moral courage in nursing. Design: Rodgers' evolutionary method of concept analysis provided the framework to conduct the analysis. Data sources: The literature search was carried out in September 2015 in six databases: PubMed, CINAHL, Scopus, Web of Science, PsycINFO, and The Philosopher's Index. The following key words were used: "moral" OR "ethical" AND "courage" OR "strength" AND "nurs*" with no time limit. After applying inclusion and exclusion criteria, 31 studies were included in the final analysis. Ethical considerations: This study was conducted according to good scientific guidelines. Results: Seven core attributes of moral courage were identified: true presence, moral integrity, responsibility, honesty, advocacy, commitment and perseverance, and personal risk. Antecedents were ethical sensitivity, conscience, and experience. Consequences included personal and professional development and empowerment. Discussion and conclusion: This preliminary clarification warrants further exploring through theoretical and philosophical literature, expert opinions, and empirical research to gain validity and reliability for its application in nursing practice.